Being misunderstood in autism: The role of motor disruption in expressive communication, implications for satisfying social relations. (2019) - Delafield-Butt, Jonathan; Trevarthen, Colwyn; Rowe, Philip; Gillberg, Christopher
Abstract: Jaswal & Akhtar's outstanding target article identifies the necessary social nature of the human mind, even in autism. We agree with the authors and present significant contributory origins of this autistic isolation in disruption of purposeful movement made social from infancy. Timing differences in expression can be misunderstood in embodied engagement, and social intention misread. Sensitive relations can repair this.